Trends and Challenges of Databases - Princz, Mária (International Journal of Engineering and Management Sciences, 2018)
The database management, using relational databases, is part of curriculum in the Hungarian high schools. The aim of this paper is to present how we can show for students the challenges facing data processing, data retrieval, beyond the relational database management taught in high school.